2011
DOI: 10.5007/2175-7925.2009v22n2p137
|View full text |Cite
|
Sign up to set email alerts
|

Registro recente, redução de distribuição e atuais ameaças ao veado-campeiro Ozotoceros bezoarticus (Mammalia, Cervidae) no Estado de Santa Catarina, Brasil

Abstract: ResumoOs campos naturais localizados na microrregião de Lages são o hábitat natural do veado-campeiro, e a localidade de Coxilha Rica, conhecida por seus campos limpos, o seu maior refúgio no Estado de Santa Catarina. Registros recentes e inéditos de veado-campeiro neste Estado são aqui publicados pela primeira vez, bem como evidências de redução de sua distribuição histórica nesta região. Em um ambiente campestre crescentemente invadido por plantios de espécies exóticas, parcelamento da terra, e queima dos ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
1
3
0
2
Order By: Relevance
“…The historical records of O. bezoarticus presented in this study were confirmed in a relict of grasslands in Santa Catarina plateau, unlike other open areas with confirmed records of O. bezoarticus, as in the region of Coxilha Rica (Mazzolli and Benedet, 2009) and Campos de Palmas (Miranda et al, 2008), which are extensive grassland formations. Based on data found in the literature (Braga 2001;Miranda et al, 2008;Mazzolli and Benedet, 2009) overlapped with grassland areas in Santa Catarina and Paraná states, a map was elaborated showing the historical distribution of O. bezoarticus, including an increase in the distribution range due to the record found in this study (Figure 3).…”
supporting
confidence: 78%
See 2 more Smart Citations
“…The historical records of O. bezoarticus presented in this study were confirmed in a relict of grasslands in Santa Catarina plateau, unlike other open areas with confirmed records of O. bezoarticus, as in the region of Coxilha Rica (Mazzolli and Benedet, 2009) and Campos de Palmas (Miranda et al, 2008), which are extensive grassland formations. Based on data found in the literature (Braga 2001;Miranda et al, 2008;Mazzolli and Benedet, 2009) overlapped with grassland areas in Santa Catarina and Paraná states, a map was elaborated showing the historical distribution of O. bezoarticus, including an increase in the distribution range due to the record found in this study (Figure 3).…”
supporting
confidence: 78%
“…According to Cherem et al (2004), it is possible that Myrmecophaga tridactyla occurs in Santa Catarina state although there are no confirmed records as it was considered rare for this state in the early 20th century (Vieira da Rosa 1905 apud Cherem et al 2004). Ozotoceros bezoarticus is confirmed to occur in Santa Catarina state (Cherem et al, 2004), and there are recent records of this species for the major grasslands of the state (Miranda et al 2008;Mazzolli and Benedet, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Para a Mata Atlântica foram levantadas 303 espécies de mamíferos terrestres, incluindo as 298 espécies listadas por Paglia et al (2012) e outras cinco citadas para o bioma por Cerqueira (1985), Freitas (2006), Mazzolli & Benedet (2009), Duarte & González (2010) e Cheida et al (2011) [Didelphis albiventris Lund, 1840 (Didelphimorphia, Didelphidae), Ctenomys minutus Nehring, 1887 (Rodentia, Ctenomyidae), Ozotoceros bezoarticus (Linnaeus, 1758) (Artiodactyla, Cervidae), Blastocerus dichotomus (Illiger, 1815) (Artiodactyla, Cervidae) e Chrysocyon brachyurus (Illiger, 1815) (Carnivora, Canidae), respectivamente]. Dentre essas 303 espécies, foram analisadas no presente estudo apenas aquelas avaliadas pela IUCN (2014), totalizando, desta forma, 276 espécies pertencentes a 10 ordens (Anexo 1).…”
Section: Obtenção Dos Dadosunclassified
“…También fueron redescubiertas pequeñas poblaciones en los estados de Paraná, Santa Catarina y Río Grande do Sul (Braga, 2004;2009;Mazzolli y Benedet, 2009). En Argentina presenta dos poblaciones aisladas, una en la región denominada como "Bajos Submeridionales", noroeste de Santa Fe ; la otra en el noreste de Corrientes, en un área de malezales y fofadales del río Aguapey (Merino y Beccaceci, 1999;Zamboni, 2011) La subespecie más austral O. b. celer Cabrera (1943), endémica del pastizal pampeano, hasta hace un siglo habitaba en toda su extensión (Jackson, 1987), sin embargo actualmente subsiste en dos poblaciones que habitan en los extremos del pastizal pampeano ( Fig.…”
Section: I2 Distribución Geográfica Del Venado De Las Pampas Subesunclassified